The Investigation of the Impact of Toxicity of Metals on Oxygen-Evolving Complex in Spinacia oleracea - Rafia Azmat; Ailyan Saleem; Waseem Ahmed; Abdul Qayyum; Hamed A. El-Serehy; Sajid Ali (Antioxidants, 2022)
The current article reported the investigation of metal toxicity on the oxygen-evolving complex (OEC) in Spinacia oleracea related to depletion in chloride ion concentration, an essential part of the photosystem (II). The greenhouse experiment was conducted where S. oleracea was cultivated in three replicates with control plants (plants “a”) treated with tap water. Moreover, 30 ppm of Cu2+ ion solution and Pb2+ ion solution was used to irrigate the rest of the plants, labeled as plants “b” and “c”, respectively, on alternative days. Advanced technologies such as Atomic Absorption Spectrophotometry (AAS), Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), and UV-visible Spectrophotometry were used to monitor the essential nutrients in leaves to validate the function of the photosystem (I and II). Reduced Cl− ions contents showed that both metals (Cu2+ and Pb2+) altered the essential elements of the oxygen-evolving complex (OEC) of photosystem (II), required to maintain the coordination structure of the Mn4CaO5 cluster. SEM analysis revealed the modified leaf structure of the S. oleracea under Cu2+ and Pb2+ accumulation due to which distorted cellular structure, reduced surface area, and the (shattered) stomatal opening compared to the plants “a” were observed. The EDS analysis of plants “b” and “c” showed high oxygen contents followed by reduced chloride contents over plants “a”, reflecting the infirmity of OEC to push out oxygen, which leads to generating oxidative stress. The lower pigment concentration in leaves of metal-contaminated plants “b” and “c” impacts carbon assimilation, which is linked to the reduced stomatal opening and influences the gaseous exchange rates. Additionally, increased contents of K+ and Ca2+ may be due to self-defense mechanisms under low chloride contents to speed up oxygen evolution to protect plants against oxidative stress. It was concluded that Cu2+ and Pb2+ metal toxicity influences essential Cl− and K+ contents, which modify the photosystem II system; subsequently, a reduced growth rate was observed.